Skin vaccination with live virus vectored microneedle arrays induce long lived CD8+ T cell memory. Issue 37 (8th September 2015) - Becker, Pablo D.; Hervouet, Catherine; Mason, Gavin M.; Kwon, Sung-Yun; Klavinskis, Linda S.
Abstract A simple dissolvable microneedle array (MA) platform has emerged as a promising technology for vaccine delivery, due to needle-free injection with a formulation that preserves the immunogenicity of live viral vectored vaccines dried in the MA matrix. While recent studies have focused largely on design parameters optimized to induce primary CD8+ T cell responses, the hallmark of a vaccine is synonymous with engendering long-lasting memory. Here, we address the capacity of dried MA vaccination to programme phenotypic markers indicative of effector/memory CD8+ T cell subsets and also responsiveness to recall antigen benchmarked against conventional intradermal (ID) injection. We show that despite a slightly lower frequency of dividing T cell receptor transgenic CD8+ T cells in secondary lymphoid tissue at an early time point, the absolute number of CD8+ T cells expressing an effector memory (CD62L−CD127+) and central memory (CD62L+CD127+) phenotype during peak expansion were comparable after MA and ID vaccination with a recombinant human adenovirus type 5 vector (AdHu5) encoding HIV-1 gag. Similarly, both vaccination routes generated CD8+ memory T cell subsets detected in draining LNs for at least two years post-vaccination capable of responding to secondary antigen. These data suggest that CD8+ T cell effector/memory generation and long-term memory is largely unaffected by physical differences in vaccine delivery to the skin via dried MA or ID suspension.